2019
DOI: 10.1371/journal.pbio.3000141
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition and maturation of SOD1 by its evolutionarily destabilised cognate chaperone hCCS

Abstract: Superoxide dismutase-1 (SOD1) maturation comprises a string of posttranslational modifications which transform the nascent peptide into a stable and active enzyme. The successive folding, metal ion binding, and disulphide acquisition steps in this pathway can be catalysed through a direct interaction with the copper chaperone for SOD1 (CCS). This process confers enzymatic activity and reduces access to noncanonical, aggregation-prone states. Here, we present the functional mechanisms of human copper chaperone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 68 publications
2
71
0
Order By: Relevance
“…3). We have recently shown disulphide subloop plasticity to also be a necessary precursor of heterodimerisation with hCCS (Sala et al, 2019). Lyons et al (1996) showed that mature Ala4Val, Gly85Arg and Gly93Ala SOD1 are less resistant to intra-subunit disulphide reduction on exposure to ascorbate than the wild-type form.…”
Section: Disulphide Bondmentioning
confidence: 99%
“…3). We have recently shown disulphide subloop plasticity to also be a necessary precursor of heterodimerisation with hCCS (Sala et al, 2019). Lyons et al (1996) showed that mature Ala4Val, Gly85Arg and Gly93Ala SOD1 are less resistant to intra-subunit disulphide reduction on exposure to ascorbate than the wild-type form.…”
Section: Disulphide Bondmentioning
confidence: 99%
“…This may highlight the importance of electrostatics stabilization of metal binding sites. Another important remark is that SOD1 can also coordinate Copper within the same binding site 42 . Hence, it could be also hypothesized that one of the monomers, or the quaternary structure, presents rather subtle but important differences that are not captured by the CG approach.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the stabilising effect of complexation with hCCS permeates further than the heterodimer interface. However, the largest structural discrepancy between mature SOD1 and that found bound to hCCS is the adoption of an induced fit disulphide sub-loop conformation at the heterodimer interface [30]. Substitution of hCCS Arg232 and Arg104 for SOD1 Ile151 and Asn19, respectively, create non-covalent interactions across the heterodimer interface with the SOD1 disulphide sub-loop.…”
Section: The Copper Chaperone For Sod1mentioning
confidence: 99%
“…hCCS domain II binds to SOD1 through an ATP-independent mechanism bringing functional hCCS domains I and III into the proximity of nascent SOD1. Full-length and domain II truncated hCCS form heterodimeric complexes with intra-subunit disulphide bond reduced wild-type SOD1 and every ALS mutant directly tested to date [29][30][31][32]. Dissociation constants of 42, 68, 35 and 33 nM have been measured for hCCS binding to metal-free Ala4Val, His80Arg, Gly85Arg and Gly93Ala mutant SOD1, respectively [31].…”
Section: The Copper Chaperone For Sod1mentioning
confidence: 99%
See 1 more Smart Citation